(untitled) (MCIT: Proceedings of International scientific and practical conference, 2025)
The article discusses complete semigroups of binary relations defined by semilattices of the class . It is described idempotent elements of complete semigroups of binary relations defined by semilattices of the class . In the case of finite semigroups, the formula for calculating idempotent elements is obtained. It is shown that the order of any subgroup of a semigroup does not exceed 2